2021
DOI: 10.1007/s10615-021-00804-0
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning in a Time of Corona: A Social Work Experience

Abstract: Preliminary results of a qualitative study of the lived experience of teaching and learning during the Covid-19 pandemic are presented. An instructor, a program director and five doctoral students in different stages of their coursework and dissertation proposal development, wrote a reflective journal. Participants varied in their levels of familiarity with technology-assisted education, personal backgrounds and circumstances including work and family responsibilities. Participants’ journals documenting their … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…However, although the pandemic provided a catalyst for innovation and a shift toward hybrid models of education, 10,11,13,14,23-25 a number of negative consequences and unresolved issues need to be addressed. 9,10,15 Our findings provide important faculty perspectives on the challenges, concerns, and priorities of faculty from a group of physical therapy education programs highly diverse in community locations, faculty and student cohort sizes, and institutional structure. Interestingly, nonparametric analysis of the magnitude of faculty challenges and concerns between different geographical regions failed to show statistically significant patterns or differences.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, although the pandemic provided a catalyst for innovation and a shift toward hybrid models of education, 10,11,13,14,23-25 a number of negative consequences and unresolved issues need to be addressed. 9,10,15 Our findings provide important faculty perspectives on the challenges, concerns, and priorities of faculty from a group of physical therapy education programs highly diverse in community locations, faculty and student cohort sizes, and institutional structure. Interestingly, nonparametric analysis of the magnitude of faculty challenges and concerns between different geographical regions failed to show statistically significant patterns or differences.…”
Section: Discussionmentioning
confidence: 88%
“…11,14 Concerns include a decrease in faculty-student engagement, inadequate depth of psychomotor learning, and issues of student anxiety and mental health. 9,10,12,15 e purpose of this article was to share the major challenges and concerns reported by faculty teaching during the COVID-19 pandemic, and the priorities believed to be necessary for programs to be better prepared for future disruptive events. is study was designed as a companion study to that of Hyland et al, 16 which reported physical therapy student perceptions of their education during the pandemic.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Among the major issues during the COVID-19 online teaching were limited students' access to technology, faculty's inability to master technology, insufficient availability of technical support, and guidance for faculty, and diverse attitudes towards completely technologymediated teaching and learning experience (McMurtrie, 2020). Furthermore, some field and labbased courses such as those in biology, chemistry, performing arts faced even more challenges in an online mode because they depend on experiential learning (Berger et al, 2021).…”
Section: Contextual Background Of Online Teachingmentioning
confidence: 99%
“…A better understanding of the experience may help in the preparedness for possible future disasters (Xia et al, 2020). The Lessons learned may help in guiding the improvement of handling the repeat of another extended transition to online teaching (Berger et al, 2021). This study focused on the use the conceptual framework of unified theory of acceptance and use of technology (UTAUT) to guide the use of M-learning to support online-teaching.…”
Section: Contextual Background Of Online Teachingmentioning
confidence: 99%